2012
DOI: 10.1016/j.pain.2011.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic receptor P2Y1 regulates polymodal C-fiber thermal thresholds and sensory neuron phenotypic switching during peripheral inflammation

Abstract: We have recently found that following complete Freund’s adjuvant (CFA) induced inflammation that cutaneous polymodal nociceptors (CPM) lacking the transient receptor potential vanilloid 1 (TRPV1) are sensitized to heat stimuli. In order to determine possible mechanisms playing a role in this change, we examined gene expression in the L2/L3 sensory ganglia following CFA injection into the hairy hindpaw skin and found that G-protein coupled purinoreceptor P2Y1 expression was increased. This receptor is of partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 34 publications
9
51
1
Order By: Relevance
“…It has been hypothesized that this phenomenon is due to altered peripheral Afiber sensitization along with improper development of glycinergic inhibition [25,27]; a notion that was recently supported by our laboratory [24]. In our previous report, we also found that developing cutaneous nociceptors were sensitized to heat and mechanical stimuli in a pattern that differed from adults [23].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…It has been hypothesized that this phenomenon is due to altered peripheral Afiber sensitization along with improper development of glycinergic inhibition [25,27]; a notion that was recently supported by our laboratory [24]. In our previous report, we also found that developing cutaneous nociceptors were sensitized to heat and mechanical stimuli in a pattern that differed from adults [23].…”
Section: Introductionsupporting
confidence: 56%
“…For P7 mice, siRNAs were injected one day before inflammation, and for P14 mice, siRNAs were injected two days before inflammation. This strategy follows a modified version of our previous reports [21][22][23].…”
Section: Sirna Production and In Vivo Nerve Injectionsmentioning
confidence: 99%
“…Conversely, both P2Y 1 and P2Y 2 mRNAs are upregulated in mouse L2/L3 DRG cells at 14 and 21 days after nerve transection [53]. The upregulation of P2Y 1 mRNA in mouse DRGs appears to be necessary for heat sensitization of cutaneous polymodal nociceptors in response to CFA injection in the skin [54]. Although the evaluation of the mRNA expression levels has been performed on total ganglia, and a contribution of glial P2Y…”
Section: Modulation Of Pain Transmission By P2y Receptors In Sensory mentioning
confidence: 99%
“…Primary afferent neurons discharge little in the absence of peripheral stimulation or injury (Jankowski et al 2012;Pitcher and Cervero 2010), and, therefore, their central terminals might be expected to have similarly low rates of neurotransmitter release in basal conditions. However, at central synapses measured in slices, neurotransmitter release occurs spontaneously, and such events are commonly viewed as arising from infrequent and stochastic release from the same pools of vesicles as action potential-evoked release (Ermolyuk et al 2013;Katz 1971).…”
mentioning
confidence: 99%